Marine Environmental Protection and Transboundary Pipeline Projects: A Case Study of the Nord Stream Pipeline - Lott, Alexander (Utrecht Journal of International and European Law, 2011)
The Nord Stream transboundary submarine pipeline, significant for its impact on the EU energy policy, has been a heav- ily debated issue in the Baltic Sea region during the past decade. This is partly due to the concerns over the effects that the pipeline might have on the Baltic Sea as a particularly sensitive large marine ecosystem.  This manuscript focuses on the issue from the viewpoint of the UNCLOS legal framework and its related treaties. It thus illustrates some of the more polemical topics arising in modern law of the sea and environmental law, eg limitations on the freedom to lay submarine pipelines, the scope and boundaries of marine scientific research, the obligation to consider alter- natives in the course of an EIA. In broader terms, this manuscript presents an explanatory study of matters mostly related to sustainable development, the precautionary principle and the ecosystem approach.